Electrochemical purification of hazardous organic compounds from wastewater by means of novel electrode materials and a solid-polymer-electrolyte-reactor system - Grimm, Jurgen Harald (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph.D.) -- University of Stellenbosch, 1999.